Tinjauan Penyebab Dispute Klaim pada Pasien Covid-19 di RSUP Dr. Sitanala Periode Mei 2020 - Februari 2021 - Hana Muta’allima; Nanda Aula Rumana; Puteri Fanya; Wiwik Viatiningsih (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Dispute claims are disagreements between facilities of health and BPJS. it can take effect on delays in services to be provided to patients. The purpose of this study was to find out the factors causing disputes over the claims of Covid-19 patients at Dr. Sitanala for the period May 2020 – February 2021. The research method used in this research is descriptive with a quantitative approach. Data collection techniques by means of interviews and observation. Percentage of claim disputes at RSUP Dr. Sitanala: in stage 1 of 63.63%. Stage 2 of 100%. Stage 3 of 12.5%. Stage 4 of 15.38%. Stage 5 of 27.27%. The total percentage of claims disputed by Covid-19 patients from stage 1 to stage 5 is 27.19%. Based on the results of the study the factors causing claim disputes, it was that patients are treated the most even though the SWAB results have been declared negative, namely 35.48%, confirmation limit is over by19.35%, patients have no significant Covid symptoms at 16.12%, accommodation billing billed inappropriately by 9.67%, evidence of intubation was not attached by 6.45%, laboratory results and other support was not attached by 6.45%, comorbid therapy was not carried out in Covid-19 patients who had comorbid diseases by 3 .22%, patient's rapid test and PCR were not attached as supporting evidence that the patient had confirmed to Covid-19 at 3.22%. SOP for the bpjs verification flow for Covid-19 patients needs to be made. Casemix staff is added so that it avoid an errors when inputting claims.